BUDIDAYA AYAM PETELUR DI KABUPATEN HALMAHERA SELATAN - Emy Saelan; Sri Lestari; Sulasmi, Sulasmi (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2024)
Cultivation of layer chickens carried out by the Kelompok Ternak Unggas Halmahera is carried out with the aim of meeting the needs of the community in meeting the need for animal protein derived from eggs and to increase the business of cultivating laying hens from a production aspect as well as an economic aspect so as to increase the income of livestock groups, especially those in Halmahera Selatan Regency. The methods used in carrying out this activity to achieve the objectives and overcome the problems faced by farmers include training in handling DOC and implementing vaccinations, training in making feed, guidance to livestock groups which is carried out on an ongoing basis, monitoring and evaluation carried out on assisted livestock groups. The results of implementing this service activity are (1) The laying hen livestock group has the ability to improve the planning of its business activities; (2) Have the ability to handle the initial arrival of DOC; (3) The livestock group has been able to make plans for work programs from the Starter to Layer periods; and (4) Ability and skills in implementing disease control